The Analysis of The Impact of Financing, Third-Party Funds, and Non-Performing Financing on The Profitability of Bank Syariah Indonesia. - Suharnanto, uja Dhiyaa’ Mutiara; Nusantara, Agung (Economics and Business International Conference Proceeding, 2024)
The research aims to investigate the effect of Pembiayaan Bagi Hasil (Participating Financing), Third-Party Funds, and Non-Performing Financing on Profitability of Islamic Banks in Indonesia for the period 2021-2024. The data collection technique used secondary sources from the official website of Islamic Banks Indonesia. The sample size is 38 data and analyzed using Eviews12 and AMOS. The research findings show: (1) Participating Financing (Ln Participating Financing) has a positive and significant effect on Profitability (2) Third-Party Funds (Ln Third-Party Funds) have a positive and significant effect on Profitability (3) Non-Performing Financing has a negative and significant effect on Profitability.